PENINGKATAN KERJASAMA DAN HASIL BELAJAR TEMATIK MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Naila Filahatin Ajria; Bambang Ismanto; Firosalia Kristin (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2018)
This research aims to: (1) to increase cooperation and thematic learning outcomes (knowledge, attitudes, and skills) grade IV SDN Blotongan 02 learning through Problem Based Learning; and (2) to describe the increase in cooperation and thematic learning outcomes (knowledge, attitudes, and skills) grade IV SDN Blotongan 02 learning through Problem Based Learning.. The type of research used is classroom action research with research subjects, namely fourth grade students of Blotongan 02 State Elementary School, totaling 34 students. Data collection techniques include observation, documentation, and written tests. Data analysis in this study uses the descriptive analysis of the qualitative and quantitative comparative analysis. On condition of prasiklus, the cooperation of students not yet optimal. After research, obtained the cooperation activities of students in cycle I, from 34 students there were 8 students (23.53%) reach the predicate